Co-existence of acute appendicitis and inflammatory myofibroblastic tumor of the small intestine: A case report. Issue 3 (September 2015) - Unver, Nurcan; Coban, Ganime; Onaran, Oyku Izel; Kunduz, Enver; Arslan, Adnan; Malya, Fatma Umit; Hasbahceci, Mustafa
Abstract Introduction Inflammatory myofibroblastic tumor as a rare neoplastic lesion is seen most commonly in the pulmonary system. Beside the presence of limited number of inflammatory myofibroblastic tumors of the gastrointestinal tract in the literature, co-existence with acute appendicitis has not been reported before. Presentation of case A 27-year-old woman admitted to emergency department with acute abdominal pain at the right lower quadrant. The initial diagnosis was as acute appendicitis. Intraoperatively, a mass with a diameter of almost 5 cm originated from the distal ileal segments neighboring the appendix was seen. The patient was managed by segmental resection of the small intestine including the mass with appendectomy. Histologically, there were bundles of spindle cells accompanied by lymphoplasmocytic infiltration. The immunohistochemical studies showed that tumor cells were positive for smooth muscle actin, vimentin, perinuclear activity for anaplastic lymphoma kinase and CD 68. The final pathologic diagnosis was inflammatory myofibroblastic tumor. Discussion Concomitant resection of tumoral lesions detected in the neighbor intestinal segments during appendectomy should be considered to diagnose and treat. For the diagnosis of inflammatory myofibroblastic tumor, immunohistochemistry pattern including positivity for actin, vimentin, CD 68 and anaplastic lymphoma kinase plays a crucial role. Therefore, detailed immunohistochemistry analysis should be performed in suspicious cases. Conclusion Coexistence of inflammatory myofibroblastic tumor located in the gastrointestinal system with acute appendicitis is a rare event. Complete surgical excision should be regarded as the mainstay of the treatment. Long-term follow up with serial imaging techniques is recommended.